2019
DOI: 10.1101/568303
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Content-based dissociation of hippocampal involvement in prediction

Abstract: Significance StatementTo deal with the noisy and ambiguous sensory signals received by our brain, it is crucial to use prior knowledge of the world to guide perception. Previous research suggests that the hippocampus is involved in predicting upcoming visual stimuli based on prior knowledge. In the current study, we show that hippocampal prediction is specific to expectations of complex objects, whereas for simple features the hippocampus generates an opposite prediction error signal instead. These findings de… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 74 publications
(88 reference statements)
2
5
0
Order By: Relevance
“…Interestingly, this selective activation of the deep layers matches that evoked by illusory Kanizsa figures, which have been suggested to be the result of an automatic structural expectation in the visual system [32]. However, since the expectations in the current experiment were signalled by a conditional cue, V1 activity is more likely to be the result of feedback from higher-order regions outside of the visual cortex, possibly involving the hippocampus [27,[50][51][52]. Speculatively, the fact that these very different types of "expectations" evoke highly similar layer-specific activity in visual cortex may point to a common computational role in V1.…”
Section: Discussionsupporting
confidence: 67%
“…Interestingly, this selective activation of the deep layers matches that evoked by illusory Kanizsa figures, which have been suggested to be the result of an automatic structural expectation in the visual system [32]. However, since the expectations in the current experiment were signalled by a conditional cue, V1 activity is more likely to be the result of feedback from higher-order regions outside of the visual cortex, possibly involving the hippocampus [27,[50][51][52]. Speculatively, the fact that these very different types of "expectations" evoke highly similar layer-specific activity in visual cortex may point to a common computational role in V1.…”
Section: Discussionsupporting
confidence: 67%
“…Interestingly, this selective activation of the deep layers matches that evoked by illusory Kanizsa figures, which have been suggested to be the result of an automatic structural expectation in the visual system (Kok et al, 2016). However, since the expectations in the current experiment were signalled by a conditional cue, V1 activity is more likely to be the result of feedback from higherorder regions outside of the visual cortex, possibly involving the hippocampus (Hindy et al, 2016;Kok and Turk-Browne, 2018;Kok et al, 2020;Schapiro et al, 2012). The fact that these very different types of 'expectations' evoke highly similar layer-specific activity in visual cortex may point to a common computational role for these expectations in V1.…”
Section: Discussionsupporting
confidence: 67%
“…For example, visual space is represented in the human entorhinal cortex in grid-type cells [117][118][119], with a subgroup of these cells firing in a direction-selective fashion prior to an upcoming saccade [120]. In line with these predictive signals in the MTL, several fMRI studies have demonstrated that the hippocampus carries predictive signals for learned sequences [121][122][123][124][125]. For example, participants in one study [121] were trained to respond to a visual cue with an action (right-or left-button press), which was then systematically associated with a specific visual outcome stimulus.…”
Section: Mechanisms Supporting Motion Processing Through Perceptual Gapsmentioning
confidence: 97%